2018
DOI: 10.3389/fpls.2018.01557
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Homologous Chromosome Pairing in a Tetraploid Intergeneric Somatic Hybrid (Citrus reticulata + Poncirus trifoliata) Revealed by Molecular Marker Inheritance

Abstract: The creation of intergeneric somatic hybrids between Citrus and Poncirus is an efficient approach for citrus rootstock breeding, offering the possibility of combining beneficial traits from both genera into novel rootstock lineages. These somatic hybrids are also used as parents for further tetraploid sexual breeding. In order to optimize these latter breeding schemes, it is essential to develop knowledge on the mode of inheritance in the intergeneric tetraploid hybrids. We assessed the meiotic behavior of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 81 publications
6
22
0
Order By: Relevance
“…LGs (LG1, LG3, LG4, LG6, and LG9), and for intermediate segregation for LG5 (PP = 0.5). A similar tendency to disomic segregation was also observed for an intergeneric allotetraploid somatic hybrid between 'Willow Leaf' mandarin and Poncirus trifoliata cv 'Pomeroy' with PP values ranging from 0.53 to 0.91 (Kamiri et al, 2018). Conversely, the PP results reported by Kamiri et al (2011) for C. deliciosa + C. limon allotetraploid somatic hybrids were lower, ranging between 0.05 and 0.71, as were those reported by Aleza et al (2016) on the meiosis of the doubled-diploid clementine where significant PP was observed for only four out of nine LGs and did not exceed 0.55, thus largely exhibiting LGS, linkage group size; GS, genome size; RR, recombination rate.…”
Section: Micrantha Dsnp Inheritance Reveals High Preferential Pairsupporting
confidence: 72%
“…LGs (LG1, LG3, LG4, LG6, and LG9), and for intermediate segregation for LG5 (PP = 0.5). A similar tendency to disomic segregation was also observed for an intergeneric allotetraploid somatic hybrid between 'Willow Leaf' mandarin and Poncirus trifoliata cv 'Pomeroy' with PP values ranging from 0.53 to 0.91 (Kamiri et al, 2018). Conversely, the PP results reported by Kamiri et al (2011) for C. deliciosa + C. limon allotetraploid somatic hybrids were lower, ranging between 0.05 and 0.71, as were those reported by Aleza et al (2016) on the meiosis of the doubled-diploid clementine where significant PP was observed for only four out of nine LGs and did not exceed 0.55, thus largely exhibiting LGS, linkage group size; GS, genome size; RR, recombination rate.…”
Section: Micrantha Dsnp Inheritance Reveals High Preferential Pairsupporting
confidence: 72%
“…However, in autopolyploids, chromosomes may have more than one possible pairing partner in the formation of bivalents. Pairing may occur randomly, leading to polysomic inheritance, or involves preferential pairing between particular chromosomes (Stift et al 2008 ; Bourke et al 2017 ; Kamiri et al 2018 ). Furthermore, an individual chromosome may pair with one or more homologous chromosomes at the same time, leading to the formation of multivalents (Sybenga 1975 ; Lloyd and Bomblies 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The particular mode of inheritance involving multivalent and/or bivalent chromosome pairing has been investigated in many autotetraploid species using a combination of molecular marker data and cytogenetic analyses (Soltis et al 1993 ; Stift et al 2008 ; Stift et al 2010 ; Kamiri et al 2018 ). In some autotetraploids including bird’s-foot trefoil (Fjellstrom et al 2001 ), blueberry (Qu et al 1998 ) and kiwi (Wu et al 2014 ), chromosomes pair and recombine exclusively or almost exclusively as bivalents, with quadrivalent formation occurring rarely (<10%).…”
Section: Introductionmentioning
confidence: 99%
“…In cases where parents are divergent, but have retained enough homology to prevent exclusive preferential pairing, inheritance patterns intermediate between di-and tetrasomic can be expected (Jeridi et al 2012;Stebbins 1947;Stift et al 2008;Sybenga 1996). Intermediate inheritance patterns have been revealed in citrus allotetraploid somatic hybrids (Kamiri et al , 2018 and for the tetraploid 'Clemenules' clementine ). Stift et al (2008) developed a likelihood-based approach to evaluate whether disomic, intermediate, or tetrasomic inheritances best fitted the segregation of genetic markers and to estimate preferential pairing and double reduction (DR) rates.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The results showed that tetraploid 'Mexican' lime has intermediary inheritance with a preferential disomic trend. In addition, Kamiri et al (2018) assessed the meiotic behavior of an intergeneric tetraploid somatic hybrid resulting from symmetric protoplast fusion of diploid C. reticulata and diploid Poncirus trifoliata, and observed an intermediate inheritance with a preferential disomic trend. On the other hand, the genotyping of the triploid progeny derived from a cross between diploid pummelo (C. maxima) and an allotetraploid intergeneric somatic hybrid between C. reticulata and C. limon showed a tetrasomic and intermediate inheritance for this citrus interspecific somatic hybrid .…”
Section: Preferential Pairing (Pp) and Maximum Double Reduction (Dr)mentioning
confidence: 99%